👤

(25b^6)^-3/2 simply ​

Sagot :

SIMPLIFYING EXPRESSIONS

Remember:

  • a^b/c = c√a^b
  • To simplify algebraic expressions make sure that there is no negative exponents and it is in simpliest form.
  • exponent that is raised to another exponent can be solved by multiplication.

Given:

  • (25b^6)^-3/2

First multiply the exponents:

25¹ = 1 x -3/2

= -3/2

b^6 = 6 x -3/2

= 3 x -3 = -9

Now, If there is a negative exponent it will be placed in the denominator or numerator (to its reciprocal)

Example:

  • a^-1 = 1/a
  • b^2 c^-3 = b²/c³

Back to the expression:

  • 25^-3/2 • b^-9
  • 1 / 25^3/2 b^9

25^3/2 = 2√25³

= √15625

= 125

FINAL ANSWER

[tex] \: \: \: \: \: \: \: \: \: \: \tt \: { \green {\boxed { \frac{1}{125b^{9} } }}}[/tex]

#CarryOnLearning